Development of Monitoring Tower Using Gyroscope Sensor Based on Esp32 Microcontroller - Al Imran; Muliaty Yantahin; Abd Muis Mappalotteng; Muh Arham (Journal of Applied Engineering and Technological Science (JAETS), 2022)
This research is a research and development research that aims to find out the results of the development of tower slope monitoring tools using the ESP32 Microcontroller-Based Sensor Gyroscope and find out the test results of the tool tower tilt monitoring using the ESP32 Microcontroller-Based Gyroscope Sensor. The development model used in this study is a prototyping model with stages of collecting needs, building prototypes, evaluating prototypes, coding s i stem, testing sistem, evaluation sistem, use s istem. The data used are interviews, questionnaires, observations and measurements. The data were analyzed using descriptive statistical analysis techniques. Based on the results of this study, a prototype of a tower slope monitoring tool was produced that was used to monitor the slope of the tower remotely through the telegram application. From the test results of the tower tilt monitoring tool using the MPU6050 gyroscope sensor based on the ESP32 microcontroller, it was found that the average time it takes to receive notifications if they occur the slope is 3.21 seconds. The results of the pecan test n there is a difference in the angle read at a height of 1 meter is 0.3 degrees, a height of 2 meters 0.2 degrees, a height of 3 meters 0.22 degrees, and a height of 4 meters 0.18 degrees. The results of the functional suitability test show that the tool functions as designed. The usability characteristic of the tower slope monitoring tool gets an average score of being included in the excellent category.